Spray-dried plasma protects against rotavirus-induced gastroenteritis via regulating macrophage and T cells divergence in weanling pigs - Yan, Hui; Dong, Biqiong; Li, Xipeng; He, Jun; Yu, Bing; Mao, Xiangbing; Yu, Jie; Luo, Yuheng; Luo, Junqiu; Wu, Aimin; Pu, Junning; Wang, Quyuan; et al. (Frontiers in Veterinary Science, 2024)
Infectious gastroenteritis is the major cause for diarrhea in piglets. The protection of spray-dried plasma (SDP) on viral gastroenteritis during the progression of rotavirus (RV) infection remain unclear. In this study, 64 weanling piglets were randomly assigned to control diets (n = 40) and SDP diets (n = 24) for 14 days, and then pigs were challenged with RV on day 15. Pigs were sacrificed on day 14 (normal condition), day 18 (manifestation stage), and day 21 (convalescent stage) of the trial. Prior to RV infection, SDP increased ADG, M1 macrophages and CD4+ T cells in different organs without increasing proinflammatory cytokines, indicating a more robust immunity with less inflammation. During the manifestation of infection, SDP enhanced mucosal immunity by increasing M1 macrophages, M1/M2 ratio and cytokines in mucosa and increasing intraepithelial CD8+ T cells for RV clearance. During the convalescence, SDP promoted M2 macrophage polarization and reduced pro-inflammatory cytokines to facilitate intestinal repair and prevent prolonged inflammation. Collectively, SDP enhanced mucosal immunity to promote viral clearance and maintained immune homeostasis to prevent long-lasting inflammation as a therapeutically approach for infectious gastroenteritis.